2004
DOI: 10.1023/b:brea.0000019966.97011.4d
|View full text |Cite
|
Sign up to set email alerts
|

Perillyl Alcohol Inhibits Human Breast Cancer Cell Growth in vitro and in vivo

Abstract: The effect of monoterpene perillyl alcohol (POH) on cell growth, cell cycle progression, and expression of cell cycle-regulatory proteins in estrogen receptor (ER)-positive (KPL-1 and MCF-7) and ER-negative (MKL-F and MDA-MB-231) human breast cancer cell lines was examined. POH inhibited cell proliferation in a dose-dependent manner in all cell lines tested. POH at a dose of 500 micro M had a cytostatic effect, in which growth inhibition was due to accumulation of cells in G1-phase. Cell cycle progression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 23 publications
2
35
0
2
Order By: Relevance
“…Previous studies showed that POH is able to exert cytotoxic effects in cancer cells, although concentrations approaching the millimolar range were required (34,35). We therefore tested whether simply mixing the 2 compounds TMZ and POH could mimic the effects of the T-P conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that POH is able to exert cytotoxic effects in cancer cells, although concentrations approaching the millimolar range were required (34,35). We therefore tested whether simply mixing the 2 compounds TMZ and POH could mimic the effects of the T-P conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…Perillyl alcohol (POH) which is the hydroxylated analogue of d-limonene, has the ability to interfere with angiogenesis (Loutrari et al, 2004). POH either alone or with PA (perillic acid, the major metabolite of POH in the body), has a potential use as an anticancer drug that stimulates different types of tumors to apoptosis, inhibits their proliferation, or overcomes their resistance to chemo-/radiotherapy (Yuri et al, 2004;Samaila et al, 2004;Elegbede et al, 2003;Clark et al, 2003;Ahn et al, 2003;Bardon et al, 2002;Burke et al, 2002;Bardon et al, 1998). The antitumor activity of POH emanates from its activity of modulating cellular processes that control cell growth and differentiation (Azzoli et al, 2003;Clark et al, 2002;Ariazi et al, 1999;Ren and Gould, 1998;Gould, 1997 andGould, 1995).…”
Section: Cancer Suppressionmentioning
confidence: 99%
“…POH has been shown to inhibit tumor growth in different solid tumor systems (11)(12)(13)(14)(15). As angiogenesis is a Cho et al…”
Section: Poh Affects Proangiogenic Cytokine Productionmentioning
confidence: 99%